2021
DOI: 10.3389/fpsyg.2021.626263
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Impact of Arts Engagement During the COVID-19 Pandemic: Analyses of Data From 19,384 Adults in the COVID-19 Social Study

Abstract: ObjectivesThe global COVID-19 pandemic in 2020 heavily affected the arts and creative industries due to the instigation of lockdown measures in the United Kingdom and closure of venues. However, it also provided new opportunities for arts and cultural engagement through virtual activities and streamed performances. Yet it remains unclear (i) who was likely to engage with the arts at home during lockdown, (ii) how this engagement differed from patterns of arts engagement prior to COVID-19, and (iii) whether hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
67
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 27 publications
17
67
2
Order By: Relevance
“…The association between creative activities and more enjoyable lockdown experiences is consistent with findings that creative activities are beneficial for a range of mental, social, physical, and wellbeing outcomes (Fancourt et al, 2019). The results are also consistent with a recent analysis of the COVID-19 Social Study suggesting that individual's used arts activities during lockdown as a way to regulate their emotions (Mak et al, 2021). It is possible that those who were able to engage in creative activities had other advantages, such as higher incomes, larger houses, or fewer caring responsibilities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association between creative activities and more enjoyable lockdown experiences is consistent with findings that creative activities are beneficial for a range of mental, social, physical, and wellbeing outcomes (Fancourt et al, 2019). The results are also consistent with a recent analysis of the COVID-19 Social Study suggesting that individual's used arts activities during lockdown as a way to regulate their emotions (Mak et al, 2021). It is possible that those who were able to engage in creative activities had other advantages, such as higher incomes, larger houses, or fewer caring responsibilities.…”
Section: Discussionsupporting
confidence: 88%
“…However, we found no associations with education (a marker of socio-economic status). Further, some of the typical barriers to engagement in the arts changed during lockdown as some activities shifted to a virtual platform (e.g., physical attendance, cost effective) (Mak et al, 2021), which may mean that some people had an enjoyable lockdown experience as they were able to participate in activities they would have otherwise been unable to.…”
Section: Discussionmentioning
confidence: 99%
“…Fink et al's (2021) large-scale survey, for example, showed that "is enjoyable," "puts me in a good mood," "helps me relax," "energizes me," and "reduces stress/anxiety" were the functions of music listening that increased the most during lockdown. Mak et al (2021), moreover, found that music was primarily used as approach and avoidance strategies to cope with emotions whereas digital arts, crafts, and reading were more important in improving participant's self-development. This does, however, not seriously threaten the strong prominence of additional eudaimonic motivations (Table 1).…”
Section: Hedonic Vs Eudaimonic Motivationsmentioning
confidence: 99%
“…Many saw themselves with extra time on their hands-either because they were unable to work from home or because they were freed from lengthy commuting times and commitments outside their homes. Mak et al (2021) demonstrated how people engaged in multifarious leisure activities falling into four overall categories: digital arts and writing, crafts, reading for pleasure, and musical activities. Individuals who were young, highly educated, worried about infection, used emotion-or problem-focused coping strategies, or experienced social support were overall more likely to increase their arts engagement during lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…For COVID-19 audiovisual media, researchers have constructed substantial datasets of news items from newspapers (AlAfnan, 2020 ), social media (Radwan and Radwan, 2020 ; Tayal and Bharathi, 2021 ), and television and broadcast media including streaming platforms like Spotify and YouTube (Behluli, 2020 ; Khatri et al, 2020 ; Olson et al, 2020 ). With regard to pandemic music, the Research Topic “Social Convergence in Times of Spatial Distancing” has generated the database CORONAMUSIC (Hansen et al, 2021 ), which features links to news reports and videos of online music-making and -sharing, and other contributions to the Topic document the benefits of these activities (Mak et al, 2021 ; Sarasso et al, 2021 ).…”
Section: The Sounds Of Pandemic Newsmentioning
confidence: 99%